Re‐examining our roots: Queer history and anatomy. Issue 4 (8th January 2022) - Smith, Theodore C.
Abstract: Since its establishment as one of the major authorities on the human body, Anatomy has played a crucial role in social and political spheres. In this article, I review how the history of Anatomy has intersected with queer history and how the effects of these interactions have affected queer lives today. In these historical cases, I aim to demonstrate how Anatomy has affected the social organization of human culture and society and also how society has affected anatomical knowledge in return. As this reciprocal connection between Anatomy and societal organization is elucidated, I argue that anatomists, clinicians, and educators have an ethical duty to address the connections of this history, both in our research and our classrooms. This historical tour begins in the ancient world, which established a connection between sexuality and physiology and reproduction. This is followed by an exploration of the Renaissance and Enlightenment, which highlight the connections between anatomical knowledge, the law, and social organization. The progressive and modern eras are explored next via modern research into the anatomical and biological origins of same‐sex attraction and the use of modern technology in these investigations. Finally, the article ends with a call for reform along with suggestions for future steps.